Harnessing The Power of Health Education and Technology: Unveiling Their Impact on Employee Productivity in ASEAN Countries - Dede Suleman; Muhammad Azizurrohman; Risky Angga Pramuja (Jurnal Dinamika Manajemen, 2024)
This study explores the impact of health expenditure, education levels, and technology adoption on employee productivity within ASEAN countries from 2015 to 2023. Utilizing secondary data from the World Bank, the research employs multiple regression analyses, specifically using Ordinary Least Squares (OLS), Fixed Effect Model (FEM), and Random Effect Model (REM) to provide a comprehensive understanding of these relationships. The findingsindicate that higher health expenditure, improved education levels, and greater technology adoption are all significantly and positively correlated with increased employee productivity. Diagnostic tests were conducted to ensure the validity and reliability of the models, with robust standard errors used to address heteroscedasticity. The results underscore the interconnected nature of these factors, highlighting the importance of integrated policy approaches to enhance workforce efficiency and economic growth. This study contributes to the broader literature on productivity by offering valuable insights for policymakers in ASEAN countries, emphasizing the need for coordinated investments in healthcare, education, and technology to drive sustainable development.